Masculinity in lesbian discourse: the case of butch and femme - Jones, Lucy (Routledge, 2015)
This chapter explores the ways in which a lesbian community of practice perform a ‘butch’ identity. It uses discourse analysis to consider an interaction between them, showing a shared sense of self to be produced which rejects traditional symbols of femininity. It is argued that performing a ‘butch’ identity is not the same as projecting a ‘masculine’ self; instead, butch identity is a way of challenging typical expectations about (heterosexual) women and femininity. ‘Butch’ identity is more complex than the mimicry of maleness, as it is often interpreted; instead, it allows lesbian women to perform an alternative, queer female identity.